Different fructose feeding strategies for poly(3-hydroxybutyrate) production by Yangia sp. ND199 - Huu Phong, Tran; Minh Khuong, Dang; Hop, Duong Van; Thuoc, Doan Van (Vietnam Journal of Science and Technology, 2017)
Yangia sp. ND199 is a halophilic bacterium isolated from mangrove soil sample. This strain was able to produce polyhydroxyalkanoate (PHA) from different carbon sources. Only homopolymer poly(3-hydroxybutyrate) (PHB) was synthesized when fructose was used as carbon source. The bacterium can accumulate high PHB content during exponential phase. Maximum cell dry weight (CDW) of 7.8 g/l and PHB content of 49 wt% were obtained after 27 h of cultivation in batch fermentation. High CDW and PHB content were achieved by using fed-batch fermentation with different fructose feeding strategies. The highest CDW of 78.5 g/l, PHB content of 67.5 wt%, and PHB productivity of 1 g/l/h were obtained by using two-stage fed-batch fermentation, is among the highest reported so far for PHB production by halophilic bacteria.